Novel Splicing Variant in the PMM2 Gene in a Patient With PMM2-CDG Syndrome Presenting With Pericardial Effusion: A Case Report - Slaba, Katerina; Noskova, Hana; Vesela, Petra; Tuckova, Jana; Jicinska, Hana; Honzik, Tomas; Hansikova, Hana; Kleiblova, Petra; Stourac, Petr; Jabandziev, Petr; Slaby, Ondrej; Prochazkova, Dagmar (Frontiers in genetics, 2020)
Congenital disorders of glycosylation (CDG) are a rapidly growing family of genetic diseases with the phosphomannomutase 2 (PMM2)-CDG being the most common form of CDG. Most of these monogenic diseases are autosomal recessive and have multi-systemic manifestations, mainly psychomotor retardation, facial dysmorphisms, characteristic distribution of the fat pads, and variable coagulation abnormalities. The association of fetal hydrops with CDG has been reported, and pericardial effusion was also rarely observed in patients with PMM2-CDG. Here we describe an infant boy with PMM2-CDG. The diagnosis was suspected based on inverted nipples, fat pads, and combined coagulopathy. However, the primary symptom was progressive pericardial effusion leading to patient death at the age of 3 months. Screening for CDG performed by the use of isoelectric focusing of serum transferrin showed a typical PMM2-CDG pattern. Exome sequencing revealed one common pathogenic variant (c.691G > A/p.Val231Met) and one novel variant (c.447 + 3dupA) in the PMM2 gene. Both PMM2 variants were further confirmed by Sanger sequencing in both the proband and the parents' DNA. The novel variant was predicted to result in loss of donor splice site, and the analysis at mRNA level confirmed that it leads to exon five skipping (r.348_447del) and causes premature termination of translation to the protein (p.G117Kfs∗4), therefore is classified as likely pathogenic. Although there is no curative therapy for the PMM2-CDG at the moment, the other supportive care options are available to be offered. The definite diagnosis of PMM2-CDG can also assist in the process of genetic counseling, family planning, and preimplantation genetic diagnosis.
Keywords: whole exome sequencing; pericardial effusion; PMM2-CDG; phosphomannomutase 2; novel splicing variant